1990
DOI: 10.1111/j.1600-0765.1990.tb00893.x
|View full text |Cite
|
Sign up to set email alerts
|

Gingival hyperplasia in rats induced by oxodipine ‐ a calcium channel blocker

Abstract: Oxodipine, a new calcium channel blocker, induced gingival hyperplasia in rats. This is the first time that a calcium channel blocker has been documented as resulting in gingival hyperplasia in rats. In contrast to diphenylhydantoin, the hyperplastic changes induced by oxodipine were not precipitated by any prior irritation. The histology consisted of purely fibroblastic proliferation without infiltrate of inflammatory cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…We must highlight the great number of calcium antagonists, apart from nifedipine, that are being studied and that may have an effect on the gingiva, such as verapamil (Pernu et ai. J989), nitrendipine (Brown et al 1990), felodipine (Lombardi et al 1991), oxodipine in rats (Nyska et al 1990). All of them have different chemical and pharmacological characteristics from those found in nifedipine.…”
Section: Discussionmentioning
confidence: 99%
“…We must highlight the great number of calcium antagonists, apart from nifedipine, that are being studied and that may have an effect on the gingiva, such as verapamil (Pernu et ai. J989), nitrendipine (Brown et al 1990), felodipine (Lombardi et al 1991), oxodipine in rats (Nyska et al 1990). All of them have different chemical and pharmacological characteristics from those found in nifedipine.…”
Section: Discussionmentioning
confidence: 99%
“…However, the features of cyclosporin A-induced gingival overgrowth were somewhat different from those induced by nifedipine or phenytoin, i.e., the collagenous component was more redundant in the cyclosporin A-induced gingival overgrowth than in that due to nifedipine or phenytoin ( 13) in rats and dogs (9). It has been reported that oxodipineinduced gingival overgrowth involved bulk enlargement due to fibroblastic proliferation without marked inflammatory cell infiltration in rats (15), or the lamina propria of the hyperplastic gingiva with fibroblastic and capillary proliferation covered by gingival epithelium with elongated rete pegs, acanthosis and parakeratosis in dogs (25). However, these histological changes were not observed in the gingival overgrowth induced by nifedipine in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a recent study by Nyska et a!. ( 15) showed for the first time that oxodipine, another dihydropyridine, induced gingival hyperplastic changes in rats without any inflammatory components in the gingiva, although the details still remain unclear. No study has yet investigated whether nifedipine like oxodipine induces gingival overgrowth in rats or how gingival inflammation and I or dental plaque is involved in its development.…”
mentioning
confidence: 99%
“…Among the other drugs capable to induce a gingival overgrowth, there are some calciutn ion blockers as described in humans (28)(29)(30)(31)(32)(33)(34)(35)(36)(37), dogs (38,39), and rats (40). The most investigated is nifedipine (33)(34)(35)(36)(37), It has been widely used since 1977 for the treatment and prophylaxis of aeute and chronic coronary insufficiency.…”
Section: Discussionmentioning
confidence: 99%